At the Fringes of Pride Politics: Experiences of Bisexual and Chronically Ill LGBTQ+ People in Portugal - Esteves, Mafalda; Pieri, Mara (lambda nordica, 2023)
This paper draws attention to the tensions generated within LGBTQ+ movements in Portugal. Although recent legal developments have put Portugal on the map as a European country welcoming LGBTQ+ people, on a local scale, movements have been less ready to expand their notions of inclusion within the LGBTQ+ spectrum. Drawing on two studies carried out through twenty qualitative interviews between 2017 and 2020, the authors focus on the tensions that emerge in the narratives of two groups of people: bisexual activists and chronically ill people who also identify as LGBTQ+. Both studies explore to what extent practices of exclusion are at play in Pride politics in Portugal and what forms of (in)visibility are privileged over others. The analysis uses the concepts of middle ground (Hemmings 2002) and boundary work (Egner 2017) to show how Pride politics are often oriented towards a normative definition of able-bodied, white gay and lesbian people. They also tend to exclude from public space some intersectional subjectivities, through active opposition or indirect discrimination. The paper offers a relevant perspective to reflect on the tensions generated by public action within LGBTQ+ communities, compromises between care and belonging, and the future advancements that will need to be made.